Conceptualizing Mobility Inequality: Mobility and Accessibility for the Marginalized - Hidayati, Isti; Tan, Wendy; Yamu, Claudia (Journal of planning literature, 2021)
The burgeoning landscape of literature on mobility inequalities has led to discrepancies between a conceptual understanding of mobility inequalities and its implementation in planning practice. Reviewing 270 publications across five decades, this article identifies intrinsic and extrinsic factors and approaches for understanding and analyzing mobility inequality. Using two thought experiments to critically locate variations in factors and approaches, dilemmas and challenges in addressing mobility inequality for the marginalized are exposed. The article concludes with future research directions for investigating mobility inequality.